Audit of venous thromboembolism risk for patients admitted to a palliative care inpatient unit. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - McKenna, Maria; Porteous, Anna; Andrew, Inga; Robson, Peter; Lee, Mark
Abstract : Background: A venous thromboembolism (VTE) risk assessment tool has been developed locally, in line with NICE guidelines, based upon the National Risk Assessment Model (DoH 2010). This single page document identifies key risk factors for VTE and contraindications to anticoagulation. Aims: Undertake a baseline audit of the new VTE risk assessment tool within a palliative care setting. Methods: Retrospective case note review of consecutive hospice admissions over a 3 month period, following introduction of the VTE risk assessment. Results: Forms – 58 patients were admitted during this period, 88% percent had a fully completed VTE risk assessment. Primary prophylaxis – 5 patients (9%) received primary prophylaxis with Low Molecular Weight Heparin (LMWH). The most common thrombotic risks, other than temporarily reduced mobility, were age>60y (64%) and abdominal/pelvic pathology (26%). Twenty-six patients (45%) had a contraindication to anticoagulation, the most frequent being active bleeding (16%) and cerebral tumour (12%). Secondary prophylaxis – Eight (14%) were already anticoagulated for thromboembolic disease, five with LMWH, two with warfarin and one was switched from warfarin to LMWH on admission. Malignant versus non-malignant disease – 51 patients (88%) had a malignancy. None of the seven patients without cancer received primary or secondary prophylaxis. 11% of patients with malignancy were dehydrated, 9% were obese and 16% had a history of VTE. These risk factors were not present in the non-malignant group. Discussion: Our rates of prescribing primary prophylaxis are higher than previously published data, despite similar contraindication rates. Interestingly, certain risk factors (dehydration, obesity, history of VTE) were more prevalent in the malignant patient group, despite not being cancer specific. This work reiterates that malignancy is a greater risk factor for VTE than immobility. Conclusion: Use of local, concise VTE risk assessment forms has led to high rates of compliance with guidance. Data collection is on-going.